Avaliação da geodiversidade do município de Caiapônia - GO - Lima, Andréa Maciel (2020)
The assessment of geodiversity is one of the initial and main stages in the development of geoconservation actions. It is fundamental to stablish parameters that quantify elements and locations of abiotic nature, in order to draw the attention for the richest related to the average, that is, those who have exceptional values. By doing that, it is possible to manage areas to the protection of a geoheritage and to develop activities such as geotourism and geoconservation. The municipality of Caiapônia is located at southwestern region of the state of Goiás, approximately 327 km from Goiânia, with a territorial area of 8.635,129 km2. On the tourist map of the state, the municipality is inserted in the Pegadas do Cerrado Circuit, this circuit is part of a tour integrated by six municipalities from the southwest of Goiás, which offers adventure tourism, ecotourism, culture and technology. The area is part of a region characterized by the important geological record of the Paleomesozoic period of the Paraná Basin, where the Serra do Caiapó is located, being a great hydrographic divider responsible for the drainage separation of the Araguaia and Paraná basins. The area also has an imposing geoform, Morro do Gigante Adormecido, in addition to numerous waterfalls and the occurance of fossils. In the attempt to conserve this natural heritage of exceptional beauty and scientific, educational and tourist importance, the objective of this study was to carry out the the quantitative evaluation, through the Geodiversity and Qualitative Index, through the inventory of places of geological and geomorphological interest. In the literature, several authors over the years have developed methodologies for quantifying geodiversity, whether quantitative or qualitative. The methodologies using geoprocessing techniques are being increasingly widespread due to the character of less subjectivity in the use of these techniques. To perform the index it was defined the methodology that generates a grid to overlay the set of cartographic data, such as lithology, paleontology, geomorphology, hydrography, mineral resources and pedology. For the inventory, it was defined the methodology that considers places with scientific values as the geosite and those that have the other values such as geodiversity sites. In conclusion, both assessments in the research showed to be effective, being complementary and essential for the evaluation of geodiversity of the municipality of Caiapônia and a important instrument to assist in territorial management.